2009
DOI: 10.1177/089686080902900514
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Peritoneal Dialysis: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are widely used in clinical practice. The safety and efficacy of these agents in peritoneal dialysis (PD) patients are unclear. Objectives We conducted a systematic review to study the safety and efficacy of ACEI and ARB use in PD patients. Primary outcome measures were mortality and cardiovascular (CV) events; secondary outcome measures were renal function, proteinuria, hyperkalemia, and erythropoietin require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…Our results agree with those of previous reported SRs [25,26] that demonstrated the renoprotective effects of RASIs in PD patients. RCTs included in previous SRs overlapped with those in our SR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with those of previous reported SRs [25,26] that demonstrated the renoprotective effects of RASIs in PD patients. RCTs included in previous SRs overlapped with those in our SR.…”
Section: Discussionsupporting
confidence: 93%
“…The previous SR and CPG search yielded two SRs [25,26] which contained four [10,11,15,27] and six [10,[15][16][17][18]20] RCTs in each, with two [10,15] duplicated. We thus identified eight articles from this step.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Holley et al (36) reported that race does not affect the rate of loss of renal function, but the study included only 25 nonwhite patients. In addition to race/ethnicity and gender (37,38), future studies should include as many key factors that may affect the rate of loss of residual renal function such as the type of renal replacement (39,40), BMI (38,41), arterial pressure (41)(42)(43)(44), use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (37,45,46), diuresis (41,(47)(48)(49), protein intake (42,50,51), diabetes (37,38,50,(52)(53)(54)(55), cardiovascular comorbidity (37,38,52,54,56), and others. Additional studies should also be pursued to determine the potential impact of reduced access to care and whether late initiation of dialysis results in adverse clinical and economic outcomes among different ESRD patient groups in the United States.…”
Section: Racial Differences In Loss Of Residual Renal Functionmentioning
confidence: 99%
“…In addition to fluid and sodium overload, dialysis patients are found to have increased sympathetic activity and abnormal response to RAAS, both of them result in higher incidence of hypertension and LVH. Although angiotensin-converting enzymes inhibitor (ACEI) and angiotensin II receptor blocker (ARB) have been shown to reduce CVD morbidity and mortality in the general population and high risk subjects [20][21][22], their protective effect in ESRD patients under dialysis remained uncertain [23]. Our previous study revealed that the overall mortality was significantly greater in patients who did not use an ACEI/ARB in ESRD patients on dialysis in a nationwide cohort [18].…”
Section: Several Mechanisms Of Cardiovascular Dysfunction Have Been Pmentioning
confidence: 99%